2009
DOI: 10.1007/s10888-009-9123-6
|View full text |Cite
|
Sign up to set email alerts
|

Does philanthropy reduce inequality?

Abstract: Community, Public goods, Inequality, Distribution, Philanthropy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Consistent with the literature (Vaidyanathan et al, 2011;Forbes and Zampelli, 1997;Will and Cochran, 1995;Ottoni-Wilhelm, 2010;Ottoni-Wilhelm et al, 2007) [12]- [16], we find an association in the maps as well as the Chi-square tests between attendance at religious services and income donated to charities. Similar associations are found between income donated to charities and inequality, supporting notions that philanthropy and inequality are related (Laskowski, 2011;Greve, 2009;Dasgupta and Kanbur, 2011) [17]- [19]. Regarding this variable, we believe there is a "home region" effect (Muller and Whiteman, 2009) [2] or proximity effect (Gilbert, 2009) [35], where landscapes of inequality and unhappiness are associated with people more actively making donations to charities.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Consistent with the literature (Vaidyanathan et al, 2011;Forbes and Zampelli, 1997;Will and Cochran, 1995;Ottoni-Wilhelm, 2010;Ottoni-Wilhelm et al, 2007) [12]- [16], we find an association in the maps as well as the Chi-square tests between attendance at religious services and income donated to charities. Similar associations are found between income donated to charities and inequality, supporting notions that philanthropy and inequality are related (Laskowski, 2011;Greve, 2009;Dasgupta and Kanbur, 2011) [17]- [19]. Regarding this variable, we believe there is a "home region" effect (Muller and Whiteman, 2009) [2] or proximity effect (Gilbert, 2009) [35], where landscapes of inequality and unhappiness are associated with people more actively making donations to charities.…”
Section: Discussionsupporting
confidence: 78%
“…However, other research suggests philanthropic giving might increase inequality. Dasgupta and Kanbur (2011, p. 18) [19] state, "using measures of both absolute and relative inequality, we have shown that philanthropy may actually exacerbate inequality, instead of reducing it." By giving tax credits for charitable donations, it reduces the amount of "resources available for direct redistribution" (Dasgupta and Kanbur, 2011, p. 19) [19].…”
Section: Income Inequality and Happinessmentioning
confidence: 80%
See 1 more Smart Citation
“…Lastly, in line with much of the existing empirical literature, the nature of the ‘community’ that is supposed to ‘participate’ has been left unexplored in our analysis. Dasgupta and Kanbur (, , ) have shown how differences in patterns of voluntary provision of public goods crucially affect inequality, distributive tensions and poverty levels, both within and across communities. It is conceivable that such differences, by influencing the costs of consensus‐building within a community, may also have a bearing on whether greater community participation leads to substantial improvements in decision‐making or simply creates blocking coalitions.…”
Section: Resultsmentioning
confidence: 99%
“…Building on these contributions, the impact of private provision on measured inequality has been explored by Dasgupta and Kanbur (). They show that private provision increases the absolute difference in real income between any two noncontributors relative to the difference in nominal incomes.…”
Section: Neutrality and Income Distributionmentioning
confidence: 99%